Rheological model of Creep and Relaxation in asphaltic mixtures using the transformed Carson Laplace, maxima and maple (2023)
In this article, the results of a creep and relaxation studies in asphalt mixtures are presented. Initially, a description of the conceptual model of the material and the details of the viscoelastic characterization in asphalt mixtures using the Creep